2018
DOI: 10.1038/s12276-018-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

The implications of signaling lipids in cancer metastasis

Abstract: Metastasis is the most malignant stage of cancer. Lipid metabolic abnormalities are now increasingly recognized as characteristics of cancer cells. The accumulation of certain lipid species, such as signaling lipids, due to the avidity of lipid metabolism may be a causal factor of tumor malignant progression and metastatic behavior. In this review, we first describe signaling lipids implicated in cancer migration, invasion and metastasis. Next, we summarize the regulatory signaling hubs of lipid anabolic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 114 publications
1
63
0
Order By: Relevance
“…Indeed, there is increasing literature linking lipid metabolism to cancer, 43,44 to migration and invasion, 45 but also to metastasis. 46 Bertini et al found in a study of serum metabolic profiles that altered lipid levels were associated with reduced survival of synchronously metastasized CRC patients. 16 In breast cancer, altered membrane lipid metabolism had been reported to underlie disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is increasing literature linking lipid metabolism to cancer, 43,44 to migration and invasion, 45 but also to metastasis. 46 Bertini et al found in a study of serum metabolic profiles that altered lipid levels were associated with reduced survival of synchronously metastasized CRC patients. 16 In breast cancer, altered membrane lipid metabolism had been reported to underlie disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites involved in lipid and linoleic metabolism constituted a major part of identified metabolic signature distinguishing NON from MET patients. Indeed, there is increasing literature linking lipid metabolism to cancer, to migration and invasion, but also to metastasis …”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming energy metabolism represents one of the hallmarks of cancer cells . As a core regulator of mitochondrial biogenesis and metabolism, the emerging roles of PGC‐1α implicated in tumorgenesis and progression have been gradually unraveled.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, melanoma cells metabolism was considerably affected and melanoma progression sustained by increased uptake of FAs from TME-resident adipocytes, hence revisiting FATPs as new possible targets in melanoma therapy (56). Moreover, beyond cell energetic requirements, lipid alterations can also affect lipid signaling in melanoma (57,58). Indeed, FAs can bind and activate specific nuclear receptors, i.e., PPARs, thus controlling the expression of genes involved in lipid homeostasis, oxidative stress, and inflammation (59,60).…”
Section: Metabolic Pathways In Melanomamentioning
confidence: 99%